Performance evaluation of different replica placement algorithms. (18th December 2008) - Rahman, Rashedur M.; Barker, Ken; Alhajj, Reda
One of the challenges for data replication in a Data Grid is to select the candidate sites that will host the replicas of datasets. In our earlier research (Rahman et al., 2006, May; Rahman et al., 2007, May), we propose different replica placement algorithms based on three mathematical models, i.e. p-centre, p-median and a multi-objective models. We also present a replica maintenance algorithm to relocate replicas to different sites if the performance of the replica host sites degrades significantly. In this research, we validate our replica placement algorithms with different performance metrics, e.g. total file transfer time, the number of local and remote file access, with accuracy. To evaluate our replica placement algorithms, we use a Data Grid simulator called OptorSim (Bell et al., 2003). This paper presents detailed execution flows of the replication algorithms in the simulator. The study of our replica placement algorithms is carried out using a model of the EU Data Grid Testbed 1 (Bell et al., 2003) sites and the associated network geometry. Jobs are based on the CDF use-case as described in Huffman et al. (2002).